Factors associated with quality of life among patients undergoing hemodialysis in Indonesia - Nursalam; Ika Yuni Widyawati; Ardhiles Wahyu Kurniawan; Wiwit Dwi Nurbadriyah (Universitas Airlangga, 2023)
Introduction: Chronic kidney disease patients will suffer a variety of health issues throughout their lifetimes, particularly with regard to their quality of life, whether they are receiving treatment or undergoing hemodialysis (HD). This study aimed to determine factors associated with QOL among patients undergoing HD in Indonesia. Methods: A cross-sectional study was conducted in Malang, Indonesia during August to December of 2020. The inclusion criteria were patients undergoing HD two times a week and aged over 18 years old. QOL was measured using the World Health Organization Quality of Life Brief Version (WHOQOL-BREF). Linear regression was used to determine factors associated with QOL. Results: About 150 participants agreed to join in this study (response rate: 84.4%) with their mean age 52.76 (SD=13.45). The total mean of the QOL in patients undergoing HD was 74.4 ± 27.7 with a range from 10 to 100. The highest mean score was reported for physical health (78.3 ± 24.8) and the lowest score was reported for environmental (72.6 ± 24.3). Linear regression showed that long duration of HD, hemoglobin concentration and blood urea with R2 was 34.6%. Conclusions: Longer duration of HD, low hemoglobin concentration and high blood urea were factors associated with lower QOL in patients undergoing HD. The results of the above study recommend to nurses and health workers to improve critical thinking skills, including measuring levels of urea and hemoglobin, which have an impact on the QOL of patients undergoing HD